Wczesna korespondencja Auzoniusza z Paulinem z Noli - Krynicka, Tatiana (Vox Patrum, 2016)
The article is devoted to the four letters written by Ausonius to Paulinus of Nola before the latter left Aquitania in 389 changing his style of life and provoking the deep crisis of their intimate friendship (Epist. 17-20, ed. R.P.H. Green). Ausonius writes to his pupil, admirer and friend about literary theory and practice, thanks for the gifts and favours, asks for help in an hour of need, sends him new year’s wishes. The exchange of letters provided to the famous befriended poets an opportunity to participate in the jolly literary games and to share mutual respect, admiration and love.